Cytomorphometric characterization of a population of Ceratium hirundinella fa. austriacum (Dinophyta) during a bloom in a reservoir of the Province of Buenos Aires, Argentina - Parodi, Elisa Rosalia (2007)
Ceratium hirundinella (O. F. Müller) Dujardin is a dinoflagellate frequently found in freshwater plankton in Argentina. It may form - together with cyanobacteria - massive blooms, particularly in autumn-winter. From 1997 until now, C. hirundinella appeared in Paso de las Piedras reservoir, Province of Buenos Aires, bringing about problems to the water-for-consumption potabilization process. On account of the fact that C. hirundinella is an extremely variable species, we have attempted for the first time on this species a statistical analysis of individuals during a massive bloom in May 2000. The specific aims of the present study were i) to determine the average biovolume and ii) to determine whether or not there are correlations among the dimensions of the different horns. The present statistical characterization allowed us to conclude that the studied population belongs to C. hirundinella fa. austriacum. All samples analysed had four horns. The statistical analysis of the data collected in the present study indicates that the length of the fourth horn is the one that exhibits the highest relative variance. In previous studies, no such a marked positive correlation between the lengths of the antapical and postequatorial horns was detected as that observed in our study by means of the principal component analysis.